The incidence and risk factors of portal vein system thrombosis after splenectomy and pericardial devascularization - Wu, Shengli; Wu, Zheng; Zhang, Xiaogang; Wang, Ruitao; Bai, Jigang (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: This study aimed to investigate the incidence and risk factors of portal vein system thrombosis (PVST) in patients with liver cirrhosis after splenectomy and pericardial devascularization. Materials and Methods: We retrospectively analyzed 71 patients who underwent splenectomy with pericardial devascularization for portal hypertension due to cirrhosis. Patients were categorized into Group A (n=23): early prophylactic anticoagulants therapy; Group B (n=29): late prophylactic anticoagulants therapy; and Group C (n=19): no anticoagulation therapy. Univariate and multivariate analyses of the risk factors of PVST were performed. The incidence of PVST and the effect of thrombolytic therapy were evaluated. Results: Multivariate analysis revealed a wider preoperative splenic vein diameter (≥8 mm), and lower preoperative platelet counts (<50×109/L) were significantly correlated with PVST development. The incidence of PVST in Groups A, B, and C was 26.1% (6/23), 44.8% (13/29), and 52.6% (10/19), respectively (all p>0.05). The complete resolution rate of portal, superior mesenteric, and splenic vein thrombosis was 75%, 62.5%, and 23.8%, respectively. Conclusion: A wider preoperative splenic vein diameter and lower preoperative platelet counts are independent risk factors of PVST. Early anticoagulation therapy had a tendency towards a reduced incidence of PVST, but it was not statistically significant. The complete resolution rate of splenic vein thrombosis was lower than that of portal and superior mesenteric vein thrombosis.